Determination of Factors Affecting Oxygen Saturation During Transfer From the Operating Room to the Post-Anesthesia Care Unit - Arıcı Parlak, Emine; Ilkaz, Neslihan; Ayhan, Hatice; İyigün, Emine (The European Research Journal, 2026)
Objectives: This study aimed to determine the incidence of desaturation (SpO₂ ≤94%) during the transfer of postoperative patients from the operating room to the post-anesthesia care unit (PACU) without oxygen support and to identify factors associated with desaturation. Methods: This prospective cross-sectional study was conducted between July 2023 and July 2024 in the operating room and PACU of a training and research hospital. The sample consisted of 164 patients. Data were collected using the Oxygen Saturation Assessment Form. Post-extubation oxygen saturation levels were continuously monitored with a pulse oximeter during transfer to the PACU and until discharge. Results: During transfer from the operating room to the PACU, 43.3% of patients had SpO₂ ≤94%, and 8.4% of these patients had SpO₂ <90%. Patients who developed desaturation had significantly higher mean age and body mass index (BMI) and lower preoperative SpO₂ values (P<0.001). Desaturation was significantly associated with female sex and the presence of chronic disease (P=0.032), whereas no significant association was found with smoking history or ASA score (P>0.05). In addition, desaturation was associated with general surgical procedures, the supine position, upper abdominal and thyroid surgeries, and the use of neuromuscular blocking agents (P<0.05). Conclusions: Approximately half of postoperative patients experienced SpO₂ ≤ 94% in the early postoperative period. Advanced age, higher BMI, lower preoperative SpO₂ values, comorbidities, upper abdominal and thyroid surgical incisions, and the use of respiratory-depressant neuromuscular agents were identified as key factors negatively affecting postoperative oxygen saturation.